2003
DOI: 10.1093/aob/mcg187
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Ultrastructural Diversity of Orbicules in Gentianaceae

Abstract: Minute granules of sporopollenin, called orbicules, can be observed on the innermost tangential and/or radial walls of secretory tapetum cells. Orbicules were investigated in 53 species of 34 Gentianaceae genera using light microscopy, scanning electron microscopy and transmission electron microscopy. This selection covered all different tribes and subtribes recognized in Gentianaceae (87 genera, +/-1650 species). Orbicules were found in 38 species (23 genera) distributed among the six tribes recognized in Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…Comparable with the palynological trend observed in Apocynaceae s.l. and Rubiaceae (Vinckier et al 2000, Vinckier & Smets 2002b, a similar trend is observed in Gentianaceae from genera which have monads possessing orbicules, to species which have more derived pollen dispersal units (tetrads or polyads) which lack orbicules (Table I, Vinckier & Smets 2003). However, no comparable trend in orbicule typology, as recorded in Apocynaceae s.l.…”
Section: Orbicules In Gentianalessupporting
confidence: 53%
See 1 more Smart Citation
“…Comparable with the palynological trend observed in Apocynaceae s.l. and Rubiaceae (Vinckier et al 2000, Vinckier & Smets 2002b, a similar trend is observed in Gentianaceae from genera which have monads possessing orbicules, to species which have more derived pollen dispersal units (tetrads or polyads) which lack orbicules (Table I, Vinckier & Smets 2003). However, no comparable trend in orbicule typology, as recorded in Apocynaceae s.l.…”
Section: Orbicules In Gentianalessupporting
confidence: 53%
“…& Schult. f. and Swertia perennis L. are characterised by amoeboid tapeta (Maheswari Devi 1962, Sankara Rao & Chinnappa 1983, and produce very small orbicules distributed in very low distribution densities on the locule wall surfaces (Vinckier & Smets 2003). Therefore, we suggest that presence of very small orbicules (mean: 0.2 mm), along with a very low distribution density (mean: 2 orbicules/ 25 mm 2 ), may indicate the presence of an amoeboid tapetum in a species, as sporopollenin granules have already been reported in taxa with an amoeboid tapetum by Tiwari & Gunning (1986).…”
Section: Orbicules In Gentianalesmentioning
confidence: 99%
“…Some of these characters have been systematically analysed in several other taxa of Gentianales such as Apocynaceae s.l. (Vinckier & Smets, 2002c), Gentianaceae (Vinckier & Smets, 2003) and Loganiaceae s.l. (Vinckier & Smets, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the tapetum in dicots and monocots might have different mechanisms for sporopollenin translocation. Analogies are often found between the ornamentation of the pollen exine and that of the Ubisch body wall (Hesse, 1986; Vinckier and Smets, 2002, 2003). Ubisch bodies are considered have great potential as model system to study sporopollenin deposition, since they are acellular structures, independent of cytoplasmic control (Clément and Audran, 1993; Verstraete et al, 2014).…”
Section: Discussionmentioning
confidence: 99%